Dakwah Perempuan Pada Masa Rasulullah SAW - Sarwinda, Sarwinda Sarwinda (BINA' AL-UMMAH, 2017)
AbstractThe problem of this research is how the role of women’s preaching in the era Rosululloh SAW. The use of this research is to reveal and find the answer of the problem. In designing this research, the writer uses qualitative method that based on library research, which contains of the role of women’s preaching in the era Rosululloh SAW. Sources of the research obtained from Islamic history books that reveal the problem. The data were analyzed qualitatively by inductive analysis technique. The results showed that the women condition at that era were treated like the trifle, the dignity of women is low even women as one as embarrassing creature. In the era of Rosululloh SAW, the role of women is highly venerated and the women have the same rights as men. Such as the role of women who contribute to preach and strive to help Rosululloh SAW in upholding monotheistic to all the earth’s surface.Keywords: Women, Preaching, History